IN VITRO AND MOLECULAR DOCKING ANALYSIS OF NUTMEG EXTRACT ANTIBACTERIAL ACTIVITY AGAINST Propionibacterium acnes - Angga Saputra, Yasir; Indah Puspita, Sari; Veni Putri, Nurhayati; Aida Febina, Sholeha (Pharmacoscript, 2025)
This study investigated the antibacterial activity of nutmeg (Myristica fragrans Houtt.) extract against Propionibacterium acnes  through in vitro and molecular docking approaches. The nutmeg flesh was extracted using ultrasonication with 96% ethanol, yielding 8.21% extract. Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, and steroids. The antibacterial activity was evaluated using the microdilution method, determining Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values of 0.5% and 1%, respectively. Molecular docking analysis was performed to understand the interaction between nutmeg's bioactive compounds and three essential Propionibacterium Acnes proteins: Sialidase (7LBV), lipase (5H6G), and Penicillin-Binding Protein 2 (3UPO). Among the tested compounds, myristicin showed the strongest binding affinity with 7LBV (-6.8 kcal/mol), while lignan exhibited notable interactions with 3UPO (-6.6 kcal/mol) and 5H6G (-5.9 kcal/mol). The molecular interactions were primarily stabilized through hydrophobic interactions and hydrogen bonding with specific amino acid residues. These findings suggest that nutmeg extract possesses significant antibacterial activity against Propionibacterium Acnes, potentially mediated through multiple molecular targets, supporting its development as a natural anti-acne ingredient.